Impact of increased digital use and internet gaming on nursing students' empathy: a cross-sectional study - Wan, Ling Lee; Muhammad Shyamil Rambiar, Puteri Nur Iman; Rosli, Nurin Qistina Batrisya; Nurumal, Mohd Said; Sh. Abdullah, Sharifah Shafinaz; Danaee, Mahmoud (Churchill Livingstone, 2022)
Background: The COVID-19 restrictions and quarantines had led to increased dependence and usage of digital devices for various human activities and internet gaming to the extent of risking vulnerable individuals to develop addiction towards it. Little is known on such risks among populations of nursing students and its impact on their empathy skills or trait. Objective: Determining the impact of digital use and internet gaming on empathy of nursing students undergoing remote learning during closure of learning institutions nationwide. Design: Cross-sectional online survey was conducted from October to December 2020. Settings: Two established public institutions located in Malaysia. Participants: A total of 345 nursing students pursuing diploma and bachelor nursing programs. Methods: Toronto Empathy Questionnaire (TEQ), Digital Addiction Scale (DAS) and Internet Gaming Disorder Scale-Short form (IGDS9-SF) were self-administered via Google Form™. Following principal component analysis of TEQ using IBM-SPSS™ (V-27), path analyses was performed using SmartPLS™ (V-3). Results: Despite the increased time spent on digital devices (Δ 2.8 h/day) and internet gaming (Δ 1 h/week) before and during the pandemic, the proportion of high digital users (1.4 %) and gamers (20.9 %) were low; and sizable ≈75 % had higher-than-normal empathy. Digital-related emotions and overuse of them were associated with lower empathy (β = − 0.111, − 0.192; p values < 0.05) and higher callousness (β = 0.181, 0.131; p values < 0.05); internet gaming addiction predicted callousness (β = 0.265, p < 0.001) but digital dependence correlated with higher empathy (β = 0.172, p = 0.009). Conclusions: Digital and internet gaming addiction potentially impact empathy. The negative impact of digital dependence can be attenuated by “digital empathy” – an emerging phenomenon becoming increasingly vital in digital health and communication.